Trap Magmatism and Ore Formation in the Siberian Noril'sk Region Volume 1. Trap Petrology - Ryabov, V.V.; Shevko, A.Ya.; Gora, M.P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The basis of this investigation is the petrographic and geochemical understanding of principal igneous rock types of the Noril’sk region, in order to demonstrate that these data provide unique and self-evident solutions to the problems of petrogenesis and mineralization. The results of the investigations are presented in two volumes: the first includes mainly text and the second contains illustrations. In the first volume, the state of the main problems of the genesis of igneous rocks with reference to Traps and related ore deposits is discussed, as well as short petrological descriptions of igneous complexes in the region, the mineral and geochemical diversity of the rocks, and aspects of the differentiation of basaltic melts and mineralization are described. Taking into account the vast number of publications on the petrology of Traps of the Noril’sk region, primary attention in the monograph is given to earlier unknown phenomena, as well as other aspects that are of great importance for solving genetic problems. Some exotic geologic targets such as the Mikchandinsky differentiated cover, the magnetite lava flow of the Putorana Plateau, the magmatogenic breccia of Kharaelakh and others are described in detail. The second volume contains an atlas of Rock Indications of igneous rock-types; formally identified reference rocks from all igneous complexes of the region, as well as photographs of thin sections of typical rocks and analytical tables of rocks and minerals from the key sections of sedimentary units and intrusions. Each rock type has been geochemically and petrographically analysed thereby providing a formal identity, complete with a photograph of the thin section. Photomicrographs of the rocks in this book will be a useful aid in visualizing the diversity of rock types in the Traps; each photograph reflecting a unique combination of minerals.
Volume 1: Trap Petrology -- Principal issues surrounding the trap magmatism of the Siberian Platform -- Effusive and explosive complexes in the Norilsk region -- Intrusive complexes of the Norilsk region -- Mineralogy and geochemistry of traps -- Basalt magma differentiation as a source of variety in traps -- Conclusion.
Keywords: Geology; Mineral resources; Mineralogy; Geochemistry; Geology; Mineral Resources; Mineralogy; Geochemistry